How can small satellites improve the weather forecast in Southeast Asia and Singapore in a context of climate change? - Toh, Xin Yi (Nanyang Technological University, 2024)
Southeast Asia is the world’s largest archipelago, accounting for 30% of tropical cyclones. As a result, it brings about severe impacts like torrential rains and storm surges, affecting various sectors, including agriculture and maritime industries. Therefore, accurate weather forecasting is crucial in the tropical region. However, achieving accurate weather forecasts in Southeast Asia has challenges. It is limited by inadequate satellite coverage; furthermore, existing global weather models have limitations in capturing specific weather challenges at lower latitude regions. This project explores the implementation of three State-of-the-art satellite mission concepts that aim to enhance forecasting accuracy. The missions reviewed include the Time-Resolved Observations of Precipitation structure and storm Intensity with a Constellation of Smallsats (TROPICS), Tomorrow.io’s commercial satellites, and the Earth Observing Nanosatellite Microwave (EON-MW). Using the FreeFlyer simulation software tool, the coverage patterns are assessed. Potential improvement to their coverage is proposed for data continuity in the tropical regions. The findings suggest that integrating targeted satellite missions could reduce weather gaps and improve weather forecasting reliability in Southeast Asia.